Market segmentation analysis in hospitals: A literature review - Herlin Ika Yuni Arista; Chriswardani Suryawati; Ayun Sriatmi (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Healthcare is undergoing a transformation in several key business units that require proper management. The growth of hospitals is accompanied by very high public demand for services, making hospitals compete in finding new opportunities and strategies to meet the needs of patients. To meet consumer expectations and desires, hospitals must design marketing combinations that provide value to the target consumer. Management planning serves the target market based on hospital market segmentation. Purpose: To find out the analysis of the health service market segment so that it is expected to help the marketing process in hospitals. Method: A literature review obtained through the internet, in the form of scientific research results from several sources. The population in this study is research with a focus on assessing hospital market segmentation in 2015-2023, obtained as many as 15 research articles sourced from scientific publications Science Direct, Scopus, ProQuest, Springer Link, Google Scholar, PubMed, JSTOR and Emerald Insight. The data obtained were then analyzed systematically. Results: Based on the results of the article analysis, eight articles were found in the form of quantitative research, seven articles in the form of qualitative research, and one research in the form of mixed method research.  Conclusion: This study concludes that market segmentation analysis in hospitals divided by geography, demographic, psychographic, and behavioral and supported by the right marketing mix is an effective means to improve health services according to customer needs.